Microstructural evolution and mechanical property of TC4/304 stainless steel joined by CMT using a CuSi3 filler wire. (December 2020) - Jin, Peng; Sun, Qingjie; Liu, Yibo; Li, Junzhao; Li, Fuxiang; Liu, Yue; Hou, Shaojun
Graphical abstract: Abstract: To obtain excellent spreadability under lower heat input and optimize interfacial microstructure, the spreading limited factors were analysed in wetting of liquid CuSi3 on 304ss and TC4 plates. At the CuSi3/TC4 joining side, the spreading model changed from diffusion-limited to reaction-limited with the interfacial temperature decreases which caused by the decrease of heat input. In the reaction-limited spreading, a continuously thin reaction layer (∼61 μm) was observed, consisting of Cu + Ti2 Cu3 + TiCu4 + Ti5 Si3, and TiCu + Ti2 Cu + Ti5 Si3 . In the diffusion-limited spreading, a thin reaction layer was transformed to a thick (∼125 μm) one with intricate phases, containing primarily of Ti5 Si3 + TiFe2 +Ti2 Cu3 + TiCu4, Ti5 Si3 + TiCu + AlCu2 Ti, and TiCu + Ti2 Cu therein. The spreading energy provided by the interfacial reaction (26 kJ/mol) was higher than that provided by the diffusion of Ti atoms in copper (21 kJ/mol), i.e. the spreading rate under 65 A welding current with a 0.783 KJ/cm heat input was greater than that under 70 A with a 0.853 KJ/cm heat input. The rapid spreading with a short residence time at a high temperature could reduce the thickness of the interface layer. At the CuSi3/304ss joining side, CuSi3 droplet could not wet 304ss when the heat input was lower than 0.783 KJ/cm. The wettability was gradually improved with increasing heat input, and the spreading driving force was provided by the diffusion of Fe in liquid Cu. A typical solid solution interface without crack defects presented at the CuSi3/304ss. Under the dual effects of reaction-promoted spreading at TC4 side and diffusion-promoted spreading at 304ss side, a wrap-around joint with high strength (∼407.6 MPa) was formed.